Social Construction of Sedarum Village Community on Money Politics in Village Head Elections - Amrillah, Radha; Novi Fitia Maliha (Journal of Religion, Local Politics, and Law, 2025)
This research aims to understand the social construction of the Sedarum Village community towards money politics in the village head election, how the community interprets and responds to money politics, because this money politics has been considered commonplace by the community, which leads to transactional vote buying. The phenomenon of money politics may be familiar to us, including the people of Sedarum Village. At the time of the village head election, there were two candidates for the position of village head, and both candidates gave money to the community to vote. Because in Sedarum village, it has become a tradition that every time there is an election, there must be money received, even worse, most Sedarum people receive money from the two candidates. Phenomenological theory is used to analyze the meaning of money politics from the community's point of view, and political economy theory that explains the economic motivation behind the acceptance of money politics. The results show that money politics has become a tradition that is difficult to avoid, where most people tend to accept money in exchange for voting, even people who have close connections with candidates can get more money than ordinary people. Money politics not only affects election results, but also changes the social and political structure of the village, where the financial capability of prospective village leaders is more important than the quality of leadership.